New records and synonymy in the genus Macropsidius (Hemiptera, Cicadellidae, Macropsinae) from China and description of a new Pediopsis species - Yang, Liyuan; Zhang, Yalin (Zootaxa, 2015)
Leafhopper species Macropsidius duuschulus Dlabola and M. niger Matsumura are recorded for the first time from China. Macropsidius fukangensis (Li et Xu) comb. nov. (from Macropsis) is proposed. A new species, Pediopsis bannaensis sp. nov., is described and illustrated from China and Thailand.